(untitled) (INNOVATIVE ECONOMY, 2020)
Skrypchuk P.M., Khomiuk N.L. REGULATORY AND LEGAL FRAMEWORK IN THE FIELD OF TAXATION OF ORGANIC LAND USE Purpose. The aim of the article is identification of the stages of the evolution of the payment system for the use of agricultural land and legislative and regulatory documents with the aim of developing theoretical and methodological principles of taxation in organic land use. Methodology of research. The commonly accepted methods of study in economic science are used In the course of the research, in particular: monographic, historical and logical, system and structural methods are used in determining the stages of the evolution of the system of payments for the use of agricultural land, taking into account the development of organic production in Ukraine. Findings. A systematic analysis of the evolution of the system of payment for the use of agricultural land with the purpose of forming directions of development of the legislative and normative base for taxation of organic land users has been carried out. The proposals on the development and approval of about 20 normative and legal acts are being developed, which will help to increase the competitiveness of domestic organic products and expand the external markets of its sales. After all, the domestic organic market for the time being actually develops in conditions of absolute ineffectiveness of the current legislation in the field of organic. The substantiation of harmonization and perspectives of organic land use and taxation of organic producers is formed. Originality. Identification of the stages of the evolution of the system of payments for the use of agricultural land with regard to the development of organic production in Ukraine: preparatory, transitional, formation, direct transformation, with clarification and periodization of the implementation of measures of regulatory and legal support for the payment of organic agricultural land use, which will help to take into account mistakes and develop recommendations measures for the development of organic farming in Ukraine. Practical value. The obtained research results are the basis for solving practical problems concerning the payment system in the field of organic agricultural land use and further development of legislation and standards for organic land use and production in Ukraine. Key words: system of payments for use of agricultural land; stages of evolution; organic land use; land payment; rent for state and communal property; single tax; EU Directive; Law of Ukraine.